2004
DOI: 10.1016/j.nedt.2003.11.009
|View full text |Cite|
|
Sign up to set email alerts
|

A pilot study on nurses' attitudes toward perinatal bereavement support: a cluster analysis

Abstract: Hong Kong nurses emphasized need for increased bereavement care knowledge and experience, improved communication skills, and greater hospital and team members' support. Findings may be used to improve support of nurses, to ensure sensitive bereavement care in perinatal settings, and to enhance nursing curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 19 publications
2
50
1
1
Order By: Relevance
“…Moreover 90.0% of nurses agreed to attach bereavement training programme.These findings are in agreement with Zhang and Lane [13] who pointed out that, nurses need to be knowledgeable about end of life and bereavement issues to provide quality care.Also, these findings are in accordance with (Eckerd 2009 [14][15][16] who were added that, small numbers of nurses and midwives report having had bereavement care training.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover 90.0% of nurses agreed to attach bereavement training programme.These findings are in agreement with Zhang and Lane [13] who pointed out that, nurses need to be knowledgeable about end of life and bereavement issues to provide quality care.Also, these findings are in accordance with (Eckerd 2009 [14][15][16] who were added that, small numbers of nurses and midwives report having had bereavement care training.…”
Section: Discussionsupporting
confidence: 85%
“…Tool 2: A likert scale was utilized to evaluate maternity nurses attitude regarding perinatal bereavement care (modified version): It was adopted from Chan et al (2004), and it was modified by the researcher to measure nurses' attitudes towards bereavement care using a Likert-type, 3 point scale ranging from "1 = disagree to 2 = uncertain, and 3 = agree". It was consisted of two parts; first part concerning with nurses attitude regarding importance of perinatal bereavement; it includes eight statements, while the second part measuring nurses attitude regarding factors affecting perinatal bereavement care; it also was included eight statements.…”
Section: Tools Of Data Collectionmentioning
confidence: 99%
“…All full‐time registered nurses (nurses registered with the Singapore Nursing Board) working at the study venue during the data collection period composed the target population. A power analysis assuming a 10% variation of interest, an 80% response rate, desired power of 80% and alpha of 5% indicated that the initial target recruitment should be around 800 participants . We expected a 10–15% non‐response rate from the sample, so we needed to survey around 914 nurses from the target hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Downe et al (2013) in their study on bereaved parents' experience of stillbirth suggest that an ethos of care at all levels of the organisation is central to positive staff caring behaviours. Hospital policy and meeting training needs of staff has a positive effect on attitudes towards bereavement care, demonstrated by Chan et al (2004). Caring for bereaved parents has been described as stressful for health care professionals, and there is a growing awareness of the importance of the emotional needs of health care professionals as well as parents (Kenworthy and Kirkham, 2011).…”
Section: Introductionmentioning
confidence: 99%